TRANSITION ANALYSIS AND THE ECONOMIC DEVELOPMENT OF ALBANIA DURING THE POST-TRANSITION PERIOD - Muco, Klodian; Avdulaj, Jonida; Ruspi, Ermonela (European Scientific Journal, ESJ, 2015)
After more than twenty years of transition filled with promises, mistakes, failures, and dilemmas concerning the economic challenges lying ahead, Albania has made remarkable economic progress. Based on the level of debates held between economists either in Albania or abroad, and based on what different policy makers believe, we came to the conclusion that there is still a lot of economic challenges like: inadequate reforms and various obstacles that hinder the country’s transition from communism to a developing country worthy of being a member of the EU. In this article, we will talk about the economic transition in Albania by re-evaluating the models of economic development and economic thought of development in order to find a connection between theory and practice. We will also try to evaluate the model of economic development applied in Albania, taking into consideration the different problems, what went wrong, and what needs to be done in order to have a sustainable economic development, and to deal with the economic-financial crisis which has affected our country. The final goal of this article is the contextualization of economic reflection and the analysis of economic models. This takes into consideration the main factors of the economic development of a country and its development, bearing in mind the economic situation we live in.